Optical Coherence Tomography for the Identification of a Rare Case of Keratoconus in Albino Donor Cornea - Hossein Mostafa Elbadawy; Alessandro Ruzza; Mohit Parekh; Davide Camposampiero; Marina De Rossi; Sandro Sbordone; Stefano Ferrari; Diego Ponzin (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Keratoconus (KC) is a corneal ectatic disorder characterized by irregular corneal surface elevation, interruptions in the Bowman's layer, stromal thinning and degeneration [1-3]. Irregular astigmatism and myopia can cause severe visual impairment. Oculocutaneous albinism (OCA) is a group of inherited disorders of melanin biosynthesis characterized by a generalized reduction in pigmentation of hair, skin and eyes. The inheritance pattern of albinism is autosomal recessive. Mutations in the tyrosinase [TYR] gene on chromosome 11 q14-q21 are reportedly common in most cases of OCA. The inheritance patterns of keratoconus are more complex than albinism due to the involvement of environmental factors in the incidence of KC. The most studied gene involved in KC is VSX1 gene, which is also involved in other corneal dystrophies [4]. Clinical manifestations of albinism include various degrees of congenital nystagmus, hypopigmentation and refractive errors, however, the association of albinism, keratoconus and corneal vascularisation were not reported previously.